Too Big to Nail: How Investor-State Arbitration Lacks an Appropriate Execution Mechanism for the Largest Awards. - Kuipers, Jacob A. (Tufts Archival Research Center, 2016)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: If a party to an international arbitration tribunal refuses to pay an award, then the claimants have the ability to seize assets of the party through national courts that could enforce the tribunal’s judgment. Those courts may issue orders to seize a party’s assets in their jurisdiction as a way to enforce all or part of the tribunal’s award. This presents an uphill battle for the claimants, particularly if the recalcitrant party is a sovereign entity. States have sovereign-immunity laws that prevent their national courts from seizing most assets of another state, except for those assets largely used for a commercial purpose. Although seizing such assets is possible and has been done, it is a costly and time-consuming process. As the size of the award increases, the costs and time required to seize assets increase exponentially. And when awards become especially massive, it becomes particularly difficult for the claimant to seize assets that would be valued anywhere near the award amount. The degree of difficulty becomes so large that it might not even be worth attempting to seize the defendant’s assets. Arbitration panels are likely to face more and more disputes involving higher and higher awards. Project-finance transactions and public-private partnerships, which have capital costs in the hundreds of billions of dollars, are becoming increasingly popular as investment mechanisms, particularly in developing countries. Nearly all these transactions use international arbitration in their contracts. Disputes that arise from these transactions could result in massive awards on a sizable scale. Barring adopting new investment treaties, states could be prevented from engaging in recalcitrant behavior by having the international community develop additional incentives to motivate states to comply with large awards rendered against them.